Analysis of Mangrove Density Levels Change Based on Cloud Computing on Abrasion Area in the Coast of Semarang City - Sidiq, Wahid Akhsin Budi Nur; Sanjoto, Tjaturahono Budi; Nayan, Nasir; Sriyanto; Fariz, Trida Ridho (Department of Geography Education, University of Jember, 2025)
The coastal areas of Semarang City have experienced land conversion due to development activities that threaten mangrove sustainability in recent years. The urgency of this research is the need to monitor mangrove density levels to be used as input in its management. The purpose of this study is to analyze changes in mangrove density levels and the occurrence of abrasion in time series using the Google Earth Engine cloud computing model. The research method used visual interpretation and spectral transformation of NDVI and MNDWI to identify spatial distribution, mangrove density and abrasion. The results showed that there was a significant decrease in mangrove area in 2019-2023 with an area of 111.74 hectares. Furthermore, the level of mangrove density is quite dynamic, especially for high density with a decrease in area from 2019 - 2023 with an area of 260.25 hectares, besides that the decline in high density mangroves also occurred in 2015 - 2023 with a decrease in area of 38.73 hectares. Abrasion in the research location was identified in 2 coastal villages, namely Mangunharjo Village with abrasion along 0.88 km (2015 - 2023) and Tugurejo Village with abrasion along 1.04 km, where both areas also experienced a decrease in mangrove area at a high-density level. In conlusion, there has been a decrease in the area and density of mangroves in the study site, one of which has an impact on abrasion.